ACPA IgG galactosylation associates with disease activity in pregnant patients with rheumatoid arthritis. Issue 8 (3rd April 2018) - Bondt, Albert; Hafkenscheid, Lise; Falck, David; Kuijper, T Martijn; Rombouts, Yoann; Hazes, Johanna M W; Wuhrer, Manfred; Dolhain, Radboud J E M
Abstract : Objectives: Patients with autoantibody-positive rheumatoid arthritis (RA) are less likely to experience pregnancy-induced improvement of RA disease activity (DAS28-C reactive protein (CRP)) compared with patients with autoantibody-negative RA. Anti-citrullinated protein antibodies (ACPAs) are the most specific autoantibodies for RA. We previously demonstrated that disease improvement is associated with changes in total IgG glycosylation, which regulate antibody effector function. Therefore, we sought to analyse the ACPA-IgG glycosylation profile during pregnancy with the aim to understand the lower change of pregnancy-induced improvement of the disease in patients with autoantibody-positive RA. Methods: ACPA-IgGs were purified from ACPA-positive patient sera (n=112) of the Pregnancy-induced Amelioration of Rheumatoid Arthritis cohort, a prospective study designed to investigate pregnancy-associated improvement of RA. The fragment crystallisable (Fc)glycosylation profile of ACPA-IgGs was characterised by mass spectrometry and compared with that of total IgG derived from the same patients or from ACPA-negative patients. Results: All ACPA-IgG subclasses display significant changes in the level of galactosylation and sialylation during pregnancy, although less pronounced than in total IgG. The pregnancy-induced increase in ACPA-IgG galactosylation, but not sialylation, associates with lower DAS28-CRP. In ACPA-positive patients, no such association was found with changes in the galactosylation of total IgG, whereas in ACPA-negative patients changes in disease activity correlated well with changes in the galactosylation of total IgG. Conclusions: In ACPA-positive RA, the pregnancy-induced change in galactosylation of ACPA-IgG, and not that of total IgG, associates with changes in disease activity. These data may indicate that in ACPA-positive patients the galactosylation of ACPA-IgG is of more pathogenic relevance than that of total IgG.